Nephrops discards, size composition, recruitment and directed effort of the Spanish fleets in Porcupine Bank (FU 16) - González-Herraiz, Isabel; Pérez-Contreras, María Nélida; Gómez-Suárez, Francisco Javier; Araujo-Fernández, María Hortensia (2015)
Spanish fleets have been fishing Norway lobster (Nephrops norvegicus) in Porcupine Bank for more than 45 years. Despite a huge Spanish effort descent in the area during this period, nowadays Spain is after Ireland the second country in Nephrops landings from this functional unit (12%). Nephrops discards in the Spanish fleets were traditionally considered negligible, but a revision about the issue is necessary. On the other hand, there are problems since 2005 to carry out length sampling from the fishery on the ports, since retained catch is now frozen on board. This lack of information can be addressed by length information collected by the observers on board. Concerning effort, Spain has been providing in the last decades effort data of the hake directed fleet (that collects almost all Nephrops catch) for the successive ICES working groups related to FU 16 Nephrops. New effort information more accurate and directed to Nephrops is needed. Taking into account this demands, discards rates and estimations, catch length information and Nephrops directed effort are presented on this document.